Computing the number of certain Galois representations mod p - Centeleghe, Tommaso (Journal de théorie des nombres de Bordeaux, 2011)
Using the link between Galois representations and modular forms established by Serre’s Conjecture, we compute, for every prime p ≤ 2593, a lower bound for the number of isomorphism classes of Galois representation of Q on a two-dimensional vector space over F[bar]p which are irreducible, odd, and unramified outside p.
Gesehen am 28.06.2022